Structure revision of the Penicillium alkaloids haenamindole and citreoindole. Issue 34 (24th August 2016) - Song, Fuhang; He, Hongtao; Ma, Rong; Xiao, Xue; Wei, Qi; Wang, Qinqin; Ji, Zengchun; Dai, Huanqin; Zhang, Lixin; Capon, Robert J.
Graphical abstract: Highlights: Deep-sea. Fungus. Structure revision. Haenamindole. Citreoindole. Abstract: Herein, we describe the isolation of rare alkaloids, haenamindole and citreoindole, from a South China Sea deep-sea fungus, Penicillium citrinum (MF006), and their structure revision based on detailed spectroscopic and C3 Marfey's analysis.